Comparison of Antioxidant Properties of Refined and Whole Wheat Flour and Bread - Lilei Yu (Antioxidants, 2013)
Antioxidant properties of refined and whole wheat flour and their resultant bread were investigated to document the effects of baking. Total phenolic content (TPC), 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging activity and oxygen radical absorbance capacity (ORAC) were employed to determine the content of ethanol extractable phenolic compounds. HPLC was used to detect the presence of phenolic acids prior to their confirmation using LC-MS/MS. Whole wheat flour showed significantly higher antioxidant activity than refined flour (p < 0.05). There was a significant effect of the bread-making process with the TPC of whole wheat bread (1.50–1.65 mg/g) and white bread (0.79–1.03 mg/g) showing a respective reduction of 28% and 33% of the levels found in whole wheat and refined flour. Similarly, baking decreased DPPH radical scavenging capacity by 32% and 30%. ORAC values, however, indicated that baking increased the antioxidant activities of whole wheat and refined flour by 1.8 and 2.9 times, respectively. HPLC analysis showed an increase of 18% to 35% in ferulic acid after baking to obtain whole and refined wheat bread containing 330.1 and 25.3 µg/g (average), respectively. Whole wheat flour and bread were superior to refined flour and bread in in vitro antioxidant properties.